Síntese, caracterização e aplicação eletroquímica do poli(dimetilsiloxano) funcionalizado com o grupo sulfônico - Wagner, Alberth Gomes (2019)
The development of new working electrodes with pre-established characteristics is due to the great need for simple, quick and inexpensive analytical tests to qualitatively and quantitatively determine important chemical and biological compounds at very low concentrations in the presence of interferentes, or to determine simultaneously more of two compounds. Some of these substances are ascorbic acid (AA), dopamine (DA) and uric acid (AU), which in abnormal concentrations in the human body may be related to various diseases. In this work, polymeric networks were prepared from poly(dimethylsiloxane) (PDMS), functionalizing them with the sulfonic group, through the oxidation that of the thiol group with hydrogen peroxide, with the purpose of developing an electrochemical sensor to detect ascorbic acid, uric acid and dopamine. After being prepared the polymer network was characterized by analysis of infrared spectroscopy (IR) and thermogravimetric analysis (TG). The polymer network was named PDMS/SO3H. Then the PDMS/SO3H was studied electrochemically by the techniques of cyclic voltammetry and square wave voltammetry, analyzing the electrochemical behavior of the material in order to develop an electrochemical sensor to simultaneously determine ascorbic acid, dopamine and uric acid in solution. Using cyclic voltammetry, oxidation potentials of +0,19V; +0,48V and +0,64V were obtained for AA, DA and AU. With square wave voltammetry, the oxidation potentials of +0,18V; +0,42V and +0,56V were obtained for AA, DA and AU, and the detection limits of 9,37mol L-1, 9,50µmol L-1 and 0,14µmol L-1 for AA, DA and AU.